American Heart Association COVID-19 CVD Registry Powered by Get With The Guidelines. Issue 8 (August 2020) - Alger, Heather M.; Rutan, Christine; Williams, Joseph H.; Walchok, Jason G.; Bolles, Michele; Hall, Jennifer L.; Bradley, Steven M.; Elkind, Mitchell S. V.; Rodriguez, Fatima; Wang, Tracy Y.; Morrow, David A.; Das, Sandeep R.; et al.
Abstract : Background: In response to the public health emergency created by the coronavirus disease 2019 (COVID-19) pandemic, American Heart Association volunteers and staff aimed to rapidly develop and launch a resource for the medical and research community to expedite scientific advancement through shared learning, quality improvement, and research. In <4 weeks after it was first announced on April 3, 2020, AHA's COVID-19 CVD Registry powered by Get With The Guidelines received its first clinical records. Methods and Results: Participating hospitals are enrolling consecutive hospitalized patients with active COVID-19 disease, regardless of CVD status. This hospital quality improvement program will allow participating hospitals and health systems to evaluate patient-level data including mortality rates, intensive care unit bed days, and ventilator days from individual review of electronic medical records of sequential adult patients with active COVID-19 infection. Participating sites can leverage these data for onsite, rapid quality improvement, and benchmarking versus other institutions. After 9 weeks, >130 sites have enrolled in the program and >4000 records have been abstracted in the national dataset. Additionally, the aggregate dataset will be a valuable data resource for the medical research community. Conclusions: The AHA COVID-19 CVD Registry will support greater understanding of the impact of COVID-19 on cardiovascular disease and will inform best practices for evaluation and management of patients with COVID-19. Abstract : Supplemental Digital Content is available in the text.